Seating arrangement in Althingi - Magnússon, Þorsteinn (Stjórnsýslustofnun, 2014)
Almost a century has passed since Althingi, the Parliament of Iceland, introduced, in 1916, the method of allocating seats to Members by drawing lots at the start of each session. This arrangement is not customary in any other national parliament in the world. It has never been established why this particular method of allocating seats was introduced in Althingi. Neither has it been mapped out how the allocation was conducted, what the Members thought of it nor what impact, if any, the arrangement had on the relations of Members and the workings of Althingi. This article therefore presents the first study of this subject in Iceland. The article also places the seat allocation procedure of Althingi in an international context, as the general rule in parliaments around the world is that Members are seated together in parliamentary party groups. The conclusions of the study are, among other things, that the seat allocation by lot was probably modelled on the House of Representatives of the United States Congress, where seats were allocated by lot from 1845-1913. The study also reveals that over 40 years passed until seat allocation by lot became fully established procedure in Althingi. In the Upper House seats were not allocated by lot at the great majority of sessions until 1959 and Members appear to have been mainly seated along party lines. In the Lower House it was common for some Members to exchange seats following the drawing of lots, and for some time attempts were made to introduce seating by parliamentary party, but the efforts were unsuccessful due to insufficient support. Since 1959 there has not been any disagreement regarding the drawing of lots for seats. Generally speaking, Members appear to hold the opinion that the seating arrangement in Althingi has a positive impact on personal relations, is a positive counterbalance to the division of Members into government supporters and opposition members and that the allocation of seats by lot is a fair method of assigning seats. The Althingi experience of ...